Mobilisation de la Nature en territoires autochtones : comparaison entre le Sapmi (Suède) et Eeyou Istchee (Canada) - Maraud, Simon (Université Laval, 2020)
The Sápmi (traditional territory of the Sami of Sweden) and Eeyou Istchee (traditional territory of the Cree or Eenouch of north-eastern Canada) have been contested territories for several decades in the face of an hegemonic definition of "Nature" and its legitimized practices imposed by the Quebec (and Canadian) and Swedish states. In the late twentieth and early twenty-first centuries, these two "Norths" became open laboratories for the integration of Aboriginal peoples in the governance of their territories. The thesis argues that protection of Nature has allowed the creation of new arenas in which reconfigurations of power structures might take place, thus leaving more room for Sami and Cree values and territorialities. This thesis analyzes the reappropriation of the management of protected areas in these territories in order to understand the stakes and the compromises involved. Two case studies are at the heart of this research: the UNESCO World Heritage Site of Laponia (Sweden) and the Quebec National Park of Assinica (under creation). The context of development in which the involvement of indigenous peoples in protected areas management takes place greatly complicates the process. The two case studies allow us to investigate the accession to natural resource management structures - from which the indigenous groups were previously excluded - and to reflect on the possible new forms of governance that are emerging from this accession. It is a question of understanding the relations of dominations which take place in the decolonization of these spaces of protection of Nature, and their influences on the possible structural transformations which emerge. Thèse en cotutelle Université Laval et Université de Limoges Le Sápmi (territoire traditionnel des Samis) et Eeyou Istchee (territoire traditionnel des Cris ou Eenouch) sont depuis plusieurs décennies des espaces de contestations qui se confrontent à la définition hégémonique de la Nature et des pratiques légitimes de l'environnement, imposée par les ...